Análisis e implementación de un radio - transceiver inalámbrico en la banda de 2.4ghz, para un modulo de transmisión/recepción ofdm capaz de soportar transmisiones los y nlos - Montoya Rodríguez, Dayse (2010)
This project consists of the development and implementation of a Transceiver module for a fixed wireless system as an important element of a possible solution for the unsatisfied demand of wireless systems. A transmitter/receiver module will be developed and implemented to operate in an unlicensed band (2.4GHz). The implementation and testing of this proposed module will be made using circuitry designed for a defined band and other RF devices like Minicircuits, Antennas, etc.